Perception and Performance on a Virtual Reality Cognitive Stimulation for Use in the Intensive Care Unit: A Non-randomized Trial in Critically Ill Patients - Gerber, Stephan M.; Jeitziner, Marie-Madlen; Knobel, Samuel E. J.; Mosimann, Urs P.; Müri, René M.; Jakob, Stephan M.; Nef, Tobias (Frontiers in Medicine, 2019)
Background: Newly acquired long-term cognitive impairments are common among survivors of critical illness. They have been linked to the stressful situation that patients experience in the intensive care unit (ICU). In this paper, we use Virtual reality (VR) technology to comfort critically ill patients and to reduce stress during their ICU stay. We investigate acceptance, comfort, recollection, visual perception of VR stimulation and how it affects physiological parameters. Methods: A VR head-mounted display was used to present immersive nature scenes to thirty-three critically ill cardiac surgery patients (mean age 63 years [range 32-83]). Data was collected with an eye tracker fitted inside the VR head-mounted display to measure eye movements (250 Hz) and sensors to record physiological parameters (240 Hz). Patients received VR stimulation (5 min in length) prior to ICU admission, during ICU stay, and three months after discharge. Acceptance, recollection and comfort was assessed with validated questionnaires. Results: The number of gazed meaningful objects per minute was significantly lower during the ICU session compared to pre- and follow-up session, whereas mean duration of fixation on meaningful moving objects was not different between the sessions. While respiration rate significantly decreased during VR stimulation, heart rate and blood pressure were constant. Post-ICU rating of VR acceptance during ICU stay was moderate to high and discomfort low. Recollection of VR was high [28/33 patients (84.8%)], while recollection of ICU stay was low [10/33 patients (30.3%)]. Conclusion: Eye movements indicate that patients were able to perceive and process cognitive stimulation during their ICU stay. VR was recalled better than the rest of the ICU stay and well accepted. Decreased respiration rate during stimulation indicate a relaxing effect of VR.